Chapter Cell Culture and Maintenance of the Evolutionary Forms of Trypanosoma cruzi for Studies of Parasitic Biology - Gonçalves, Moreno (InTechOpen, 2019)
This chapter aims to present and discuss the main cell culture techniques used for the growth and maintenance of the different evolutionary forms of the protozoan Trypanosoma cruzi, the etiologic agent of the Chagas disease. Chagas disease is a neglected tropical disease endemic in several Latin American countries. Here, we intend to present the main difficulties, advantages, and disadvantages of using Trypanosoma cruzi cell culture in parasitic biology. Finally, we present the main research opportunities in the context of Trypanosoma cruzi parasitic biology using cell culture techniques, such as drug development, characterization of pharmacological targets, molecular markers for diagnosis, structural biology, and many other biomedical applications.